2021
DOI: 10.1111/iju.14747
|View full text |Cite
|
Sign up to set email alerts
|

Ileal conduit versus neobladder: A propensity score‐matched analysis of the effect on renal function

Abstract: Objectives To analyze the long‐term effects of continent (neobladder) compared with incontinent (ileal conduit) urinary diversion. Methods We carried out a retrospective review of our departmental database. Estimated glomerular filtration rate was calculated using the Chronic Kidney Disease Epidemiology Collaboration equation. Neobladder and ileal conduit patients were matched in a 1:2 ratio and a propensity score‐matched analysis was carried out. Data were summarized using descriptive analysis. Trend plots we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Although some studies reported a negative impact of orthotopic neobladder on postoperative renal function [53], high-level evidence is available supporting the long-term safety of this type of diversion. Iqbal et al [54] reported similar postoperative GFR up to 5 years following RC with neobladder vs. ileal conduit. Moreover, in a large prospective randomized trial involving 484 patients undergoing RC with either a Studer or T-pouch orthotopic neobladder, the type of ileal orthotopic neobladder was not independently related to 3-year renal function [12].…”
Section: Renal Function Deteriorationmentioning
confidence: 87%
“…Although some studies reported a negative impact of orthotopic neobladder on postoperative renal function [53], high-level evidence is available supporting the long-term safety of this type of diversion. Iqbal et al [54] reported similar postoperative GFR up to 5 years following RC with neobladder vs. ileal conduit. Moreover, in a large prospective randomized trial involving 484 patients undergoing RC with either a Studer or T-pouch orthotopic neobladder, the type of ileal orthotopic neobladder was not independently related to 3-year renal function [12].…”
Section: Renal Function Deteriorationmentioning
confidence: 87%